HUMAN CHORIONIC GONADOTROPHIN (HCG) AND HYPERTHYROIDISM: RARE BUT PARALLEL CAUSE - Baskaran, SA; Tukiman, MU; Adam, II (Journal of the ASEAN Federation of Endocrine Societies, 2024)
INTRODUCTION/BACKGROUND Choriocarcinoma is a hCG-producing malignancy, with the beta subunit being structurally similar to TSH, allowing it to bind to TSH receptors on thyroid follicular cells and at high levels to elicit biochemical hyperthyroidism. CASE We report a case of choriocarcinoma-induced hyperthyroidism in a 29-year-old female. She was initially admitted for breathing difficulties and was found to have a posterior mediastinal mass, which was later histologically confirmed to be choriocarcinoma with B-HCG levels of 466,511 that peaked to 825,316. Thyroid functions measured shows TSH of 32.07, T4 of 0.009 with negative thyroid antibodies (Anti Thyroid Peroxidase <9, Anti Thyroglobulin 11.9). Ultrasonography showed bilateral thyroid nodules, ACTR TR3 (1.5 cm), however, staging CT did not pick up an overt goitre. Patient was started on carbimazole and planned for chemotherapy with thyroid function monitoring. CONCLUSION TSH and Beta-HCG are highly homologous and can cross-link to produce elevated thyroid hormone levels. The prevalence of hyperthyroidism in choriocarcinoma is not known; however, prolonged exposure to high HCG levels is required for it to occur. It is generally accepted that 25,000 IU/L of HCG is equivalent to 1 mU/L of TSH activity, with suggestions to measure thyroid function in patients with HCG >50,000 IU/L. Patients with symptomatic hyperthyroidism are treated with antithyroid drugs and the primary choriocarcinoma is treated with chemotherapy. Reduction or normalisation of the beta hCG levels quickly induces euthyroidism. Beta-HCG-induced hyperthyroidism is rare; however, with high levels found in choriocarcinoma, suspicion of concurrent hyperthyroidism should be raised. Patients with HCG-secreting tumours should be evaluated for hyperthyroidism and may benefit from treatment until the underlying cause is treated.